Effect of Cupping (Al-Hijima) on Hematological and Biochemical Parameters for some Volunteers in Missan Province - Abbas Ch. Mraisel 1 , Mustafa A. Nama2 , Ahmed, A. Habeeb3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: The aim of Cupping is to extract the blood which is believed to be harmful for the body which in turn rids the body of potential harm from symptoms leading to a reduction in stressful condition. The study was performed to evaluate the effects of cupping (Hijama) on the hematological and the biochemical parameters in the patients before and after making the cupping. Subjects and Method: The study was performed in period between (first November -2018 to May- 2019) and conducted on (30) volunteers coming to Hijama centers in different parts of Missan province in ages between (30-50) years with . Five (5ml) of venous blood samples were collected the first sample was taken before and after one week of cupping and two weeks later after cupping . Each sample of blood was separated into two tubes for hematological assessment and the serum was stored in -20°C freezer till handled for biochemical analysis ,determined lipid profile and serum electrolytes level. These parameters were performed in laboratories of Al- Sadder Teaching Hospital – Amarha City according to the standard methods that described in the Analysis Kits that used in this study was products of Spinach Company Spin react. Results: The obtained results for hematological analysis observed significant increase in (RBCs) after one and two week of making Hijima in (p< 0.05).as compared results before making hijjama ,significant decrease in haematocrit(HCT) ,hemoglobin (Hb) ,Platelets (Plt) , neutrophiles and lymphocytes percentages after one and two week of making Hijama as compared results before making hijama . Total cholesterol were observed significant decrease in (P>0.05) after one and two weeks of hijima in compared with the total cholesterol before making the hijima ,decrease in (LDL), (vLDL) and Triglyceride after one week and two week of hijima as compared before making the hijima .High density lipoprotein (HDL-ch) observed significant increase in (P>0.05) after one week and two weeks of making hijima as compared with (HDL ch) before making the hijima. The biochemical analysis observed significant decrease in levels of ALP enzyme,creatinine ,blood urea nitrogen and blood glucose in(P>0.05) after one and two weeks of Hijima, significant increase in levels of total proteins , AST and ALT in(P>0.05) after one and two weeks of making Al-hijima as compared with levels before making the hijima. Serum electrolytes level showed an significant decline in serum Calcium ions (Ca+2) in (P>0.05) after one and two weeks of making Al-hijima as compared to the serum calcium level before making of Al- hijama. Also observed insignificant decline in serum sodium(Na+2), chloride ions (Cl-) and potassium ions(K+) as compared to level of sodium ,chloride and potassium ions before making of Al- hijama.